Severe Hypercalcemia as an Initial Presentation of Advanced Hepatocellular Carcinoma: A Case Report - Bashir AM; Mohamed AH; Mohamed HN; Ibrahim IG (Cancer Management and Research, 2022)
Ahmed Muhammad Bashir,1 Abdirashid Hashi Mohamed,1 Hawa Nuradin Mohamed,1 Ismail Gedi Ibrahim2 1Internal Medicine Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan, Training and Research Hospital, Mogadishu, Somalia; 2Radiology Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan, Training and Research Hospital, Mogadishu, SomaliaCorrespondence: Ahmed Muhammad Bashir, Internal Medicine Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan, Training and Research Hospital, Mogadishu, Somalia, Email ambashir@hotmail.comBackground: It is extremely rare for hypercalcemia to appear as the first symptom of hepatocellular carcinoma. Instead, it occurs primarily as a paraneoplastic manifestation after the disease is already diagnosed.Methods: In this report, we describe a 55-year-old woman who presented with symptoms of acute severe hypercalcemia and was negative for hepatitis B surface antigen and hepatitis C virus antibodies.Results: Laboratory tests confirmed hypercalcemia (serum calcium 16.2 mg/dL) with intact parathyroid hormone (2 pg/mL). Alpha-fetoprotein serum level was 3031.14 ng/mL. Abdominal ultrasonography and computed tomography revealed a big vascularized mass of 7 × 5.5cm in diameter, occupying most of the right lobe of the liver.Conclusion: Based on these findings, hepatocellular carcinoma may present late in disease progression with isolated hypercalcemia; therefore, HCC should be considered in the differential diagnosis in a hypercalcemic patient.Keywords: hypercalcemia, hepatocellular carcinoma, Somalia